2006
DOI: 10.1021/jm060108a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Pharmacological Evaluation of Novel Nitrobenzenic Thromboxane Modulators as Antiplatelet Agents Acting on Both the Alpha and Beta Isoforms of the Human Thromboxane Receptor

Abstract: Thromboxane A(2) (TXA(2)) is an arachidonic acid metabolite involved in pathologies such as stroke, myocardial infarction, and atherosclerosis. Consequently, the design of TXA(2) receptor (TP) antagonists remains of great interest in cardiovascular medicine. The actions of TXA(2) are mediated by its specific G-protein coupled receptor of which two alternative spliced isoforms, TPalpha and TPbeta, have been described in humans. In this study, we report the synthesis of a series of original N-alkyl-N'-[2-(cycloa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…TXA 2 synthase inhibitors and TP receptor antagonists have been developed as anti-asthma drugs, and demonstrated to improve TP receptor-induced airflow limitation and bronchial hyperresponsiveness (Hanson et al, 2005;Ishimura et al, 2008;McKenniff et al, 1991). However, the signaling pathway responsible for modulation of TP receptor mediated airway hyperresponsiveness to TXA 2 is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…TXA 2 synthase inhibitors and TP receptor antagonists have been developed as anti-asthma drugs, and demonstrated to improve TP receptor-induced airflow limitation and bronchial hyperresponsiveness (Hanson et al, 2005;Ishimura et al, 2008;McKenniff et al, 1991). However, the signaling pathway responsible for modulation of TP receptor mediated airway hyperresponsiveness to TXA 2 is not clear.…”
Section: Introductionmentioning
confidence: 99%
“…At 2 h post injection, the majority of tissues and organs showed significant decreased in 99m Tctricarbonyl UDCA uptake. On the other hand, lung and intestine showed significant increase in 99m Tc-tricarbonyl UDCA uptake [20]. There were gradual increase of liver and intestine uptakes through experiment time points, which indicated that the clearance mechanisms of these complexes were through the renal and hepatobiliary path way where the urine was increase from13.5 ± 0.005 at 30 min into 45.57 ± 0.33 at 2 hr.…”
Section: Stability In Serummentioning
confidence: 88%
“…The formed complex remained stable with increasing the amount of valsartan up to10 mg. So the optimum amount of valsartan was kept at 2 mg [13,14].…”
Section: Effect Of Valsartan Amountmentioning
confidence: 99%